Dysregulated mitochondrial metabolism upon cigarette smoke exposure in various human bronchial epithelial cell models - Christy B. M. Tulen; Ying Wang; Daan Beentjes; Phyllis J. J. Jessen; Dennis K. Ninaber; Niki L. Reynaert; Frederik-Jan van Schooten; Antoon Opperhuizen; Pieter S. Hiemstra; Alexander H. V. Remels (The Company of Biologists, 2022)
Exposure to cigarette smoke (CS) is the primary risk factor for developing chronic obstructive pulmonary disease. The impact of CS exposure on the molecular mechanisms involved in mitochondrial quality control in airway epithelial cells is incompletely understood. Undifferentiated or differentiated primary bronchial epithelial cells were acutely/chronically exposed to whole CS (WCS) or CS extract (CSE) in submerged or air-liquid interface conditions. Abundance of key regulators controlling mitochondrial biogenesis, mitophagy and mitochondrial dynamics was assessed. Acute exposure to WCS or CSE increased the abundance of components of autophagy and receptor-mediated mitophagy in all models. Although mitochondrial content and dynamics appeared to be unaltered in response to CS, changes in both the molecular control of mitochondrial biogenesis and a shift toward an increased glycolytic metabolism were observed in particular in differentiated cultures. These alterations persisted, at least in part, after chronic exposure to WCS during differentiation and upon subsequent discontinuation of WCS exposure. In conclusion, smoke exposure alters the regulation of mitochondrial metabolism in airway epithelial cells, but observed alterations may differ between various culture models used. This article has an associated First Person interview with the joint first authors of the paper.